AN ATTEMPT TO DEVELOP XI MIPA STUDENTS’ SELF-CONFIDENCE THROUGH GROUP PRESENTATION METHOD - Naibaho, Elnifa; Megawati Tammu, Reisky (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
A student's self-confidence is indispensable in learning and provides a positive impact in the form of courage, activeness, and self-actualization during the teaching and learning process. In fact, the facts in the research field indicate that not all students of XI MIPA class have good self-confidence like students’ courage lack in giving opinions and asking questions that are still confusing. In addition, students’ lack of self-confidence is caused by several factors, either internal or external. The solution as an attempt to develop students' self-confidence is through the application of the group presentation method. The research method used is descriptive qualitative through an instrument in the form of a portfolio of Field Experience Program activities, which consists of observation sheets, observation and teaching reflections, google forms, lesson plans, presentation assessment results in the form of rubrics, and students’ self-confidence questionnaires. The results indicate that applying the group presentation method is able to develop the XI MIPA students’ self-confidence. Students' self-confidence can be developed through the presentation method through the stages of forming groups, dividing topics, making discussions, and group presentations. Self-confidence as the indicator that was observed after the application of the group presentation method are students who can express opinions, ask questions, and are able to adapt themselves. Suggestions for further research are that teachers can encourage students to write reflections related to the development of students’ self-confidence during the learning process.